Additional Cover. Issue 11 (2nd November 2022) - Wang, Zejing; Lu, Hao; Tang, Tao; Liu, Lei; Pan, Bohan; Chen, Jiqiu; Cheng, Dasheng; Cai, Xiaoxiao; Sun, Yu; Zhu, Feng; Zhu, Shihui
Abstract : The cover image is based on the Original Article Tetrahedral framework nucleic acids promote diabetic wound healing via the Wnt signalling pathway by Zejing Wang et al., https://doi.org/10.1111/cpr.13316 .